Identifying the correlation between the number of OGTT abnormalities and perinatal outcomes in twin pregnancies: a retrospective cohort study - Li, Jia-Zheng; Chen, Hong-Yu; Liu, Tai-Hang; Tang, Wei-Zhen; Wang, Lan; Wen, Li; Wang, Ying-Xiong; Zhang, Zi-Heng; Cai, Qin-Yu; Zhou, Ni-Ya; Ye, Kai (Frontiers in Endocrinology, 2025)
IntroductionGestational diabetes mellitus (GDM) is a common metabolic disorder during pregnancy and is particularly significant in twin pregnancies due to their inherently higher risk of adverse perinatal outcomes. Identifying the correlation between the degree of glucose intolerance and perinatal outcomes can provide valuable insights for clinical management. This study aimed to investigate the risk of developing adverse perinatal outcomes in pregnant women and fetuses with twin births by the number of abnormal values of oral 75 g glucose tolerance test (OGTT).MethodsWe conducted a population-based retrospective cohort study in which 3545 pregnant women with twin pregnancies in Women’s and Children’s Hospital of Chongqing Medical University underwent an oral 75 g glucose tolerance test to collect fasting, 1-hour postprandial, and 2-hour postprandial glucose, and to collect the perinatal outcomes of pregnant women and fetuses in the set.ResultsLogistic regression analysis showed that the number of abnormal OGTTs was associated with the risk of expected adverse perinatal outcomes. In the unadjusted model, the prevalence of gestational hypertension, intrahepatic cholestasis in pregnancy, and hypoproteinemia in pregnancy were statistically significant. In the adjusted model, the prevalence of gestational hypertension and intrahepatic cholestasis in pregnancy was statistically significant.ConclusionsThe number of abnormal OGTTs was associated with the incidence of gestational hypertension and intrahepatic cholestasis in pregnancy in twin pregnancies that had undergone assisted reproduction. These findings highlight the importance of closely monitoring glucose levels in such pregnancies to mitigate associated risks.